The Task of the Survivor in Ruth Klüger’s «weiter leben» (1992) and «Still Alive» (2001) (Studia austriaca, 2013)
Ruth Klüger’s German and English memoirs provide a unique opportunity to consider intersections between memory, survival, and self-translation. A Benjaminian interpretation of Klüger’s memoirs, weiter leben: Eine Jugend (1992) and Still Alive: A Holocaust Girlhood Remembered (2001), addresses the question of what meanings accrue to survival as it unfolds over 50 years and in two memoirs and languages. Echoing the ethical interventions articulated by Benjamin in «The Task of the Translator», I identify the ways in which Still Alive asserts itself as a translation.